FGreen Inc Business Plan - Li, Lirong (2016)
This Plan introduces the plan of developing a new product that adopting the new technology, follows by the thorough analysis such as needs analysis and competitor analysis. It provides rigorous strategies to guide the business idea, and offers conservative financial projections. It ends by detailed SWOT analysis and risks analysis, as well as the risk management.